The Need For Love And Belongingness In Jennifer Crusie`S Anyone But You (1996): A Humanistic Psychological Approach - Yostin, Ganang; , Dr. M. Thoyibi, M.S; , Titis Setyabudi, S.S. M.Hum (2015)
The objective of the study is, first, is analyzing the novel based on the structural elements, and the second is analyzing the issue of the need for love and belongingness by using humanistic psychological approach. The methods to conduct this research are determining the type of the study, determining the object of the study, determining the data sources, determining the technique of data collection, and determining the technique for data analysis. This research is a descriptive qualitative research. The primary data data sources is Jennifer Crusie`s Anyone But You (1996) novel. The secondary data sources are books, journals, and internet sources related to the study. The two kinds of data collected through library research and analyzed with descriptive analysis. The researcher draws two conclusions. First, the structural element of the novel described the character and characterization, setting of time and place, plot, point of view, and theme. They shape into one unity. Second, based on humanistic psychological approach, the need for love and belongingness was revealed with other descriptions of physiological and safety needs that reflected in the novel.